THE EFFECTS OF THE UTILIZATION OF INTEGRATED MANAGEMENT POST OF MEDICAL FACULTY OF MULAWARMAN UNIVERSITY ON RISK INDICATORS OF NON-COMMUNICABLE DISEASE - Irma Kania Safitri; Krispinus Duma; Rahmat Bakhtiar; Evi Fitriani (Universitas Muhammadiyah Kalimantan Timur, 2019)
Non-communicable diseases have become a major public health problem in the last decade. In Indonesia, it was more than 36 million people dying from non-communicable diseases related to several risk factors including behavioral, metabolic and social risk factors. Several indicators can be considered to detect the risk factors of non-communicable diseases. They are blood pressure, cholesterol, glucose, uric acid, and body mass index. Efforts to prevent and control non-communicable diseases that are being developed in Indonesia are integrated management posts for non-communicable diseases that provide facilities and guidance to the community to take part in controlling the risk factors for non-communicable diseases. This research is an observational analytic study with the cross-sectional method based on data obtained from the monitoring book of members of the Medical School of Mulawarman University. The sample of this study was all individuals in the population that met the inclusion criteria of the study. Sixty-five samples were obtained to see the posbindu effect on blood pressure and 61 samples saw the effect of posbindu on total cholesterol levels that met the inclusion criteria. The variables observed in this study were posbindu utilization, sample blood pressure, and total cholesterol levels in the sample. The results of the research, there was the effect of using posbindu on sample blood pressure (p = 0.042), and there was no effect on the use of total cholesterol level in the sample (p = 0.590).